Preparation of porous CuO films from Cu(NO3)2 aqueous solutions containing poly(vinylpyrrolidone) and their photocathodic properties. Issue 29 (24th March 2017) - Uchiyama, H.; Isobe, K.; Kozuka, H.
Abstract : We prepared porous CuO photocathode films by dip coating from Cu(NO3 )2 aqueous solutions containing poly(vinylpyrrolidone). The porous structure led to an efficient photocathodic reaction under the UV and visible light illumination. Abstract : We prepared cupric oxide (CuO) photocathode films by dip coating from Cu(NO3 )2 aqueous solutions containing poly(vinylpyrrolidone) (PVP). The addition of PVP modified the wettability of FTO glass substrates by the aqueous coating solutions, resulting in the formation of CuO coating layers on the substrates. The thermal decomposition of PVP by provided nanoscale pores in the resultant CuO films, and the porosity increased with increasing PVP content. The porous structure thus obtained led to an efficient photocathodic reaction under UV and visible light illumination (wavelength: 300–800 nm). Highly porous CuO films prepared at [PVP] = 0.25 M exhibited the maximum incident photon-to-current efficiency (IPCE) values of 8.7% and 3.9% at 300 and 500 nm, respectively.